Gluten‐free diet modulates inflammation in salivary glands and pancreatic islets. (2nd February 2021) - Haupt‐Jorgensen, Martin; Groule, Vibeke; Reibel, Jesper; Buschard, Karsten; Pedersen, Anne Marie Lynge
Abstract: Objectives: A lifelong gluten‐free (GF) diet ameliorates autoimmune diabetes in non‐obese diabetic (NOD) mice and most likely in humans. Besides diabetes, NOD mice develop focal sialadenitis, as seen in Sjögren's syndrome (SS). In humans, type 1 diabetes (T1D) is also linked to SS. Here, we investigated whether a lifelong GF diet influences the immune cell infiltration in the salivary glands and pancreatic islets in NOD mice. Methods: NOD mice were fed a lifelong (i.e. 13 weeks) GF or gluten‐containing standard (STD) diet. Insulitis and sialadenitis were scored on H&E‐stained paraffin‐embedded sections of pancreas and submandibular glands. Immune cell specificity and distribution were investigated immunohistochemically. Results: There were fewer CD68+ and CD4+ cells in submandibular gland areas with focal sialadenitis as well as reduced insulitis and fewer VEGFR2+ cells in pancreatic islets in mice on GF versus STD diet. The degree of sialadenitis was not significantly lower in GF mice, but sialadenitis and insulitis correlated strongly. Lung weight was lower in GF mice. Conclusion: In NOD mice, a lifelong GF diet reduces infiltration of monocytes/macrophages and T cells in salivary glands and inflammation in pancreatic islets, possibly by reducing VEGFR2, indicating that the linked autoimmune diseases, T1D and SS, may be alleviated by a GF diet.